The right to health on accessibility to medicines and health services: A comparative study of Iranian Laws and international documents - Shahriar Eslamitabar; Seyed Mohammad Hashemi; Abbas Kebriyaeezadeh; Mohammad Javad Rezaiezadeh (Tehran University of Medical Sciences, 2017)
Background: Right to health has always been one of the main concerns of human beings and based on international standards and documents, it is considered as an important part of human right. Today, right to health on accessibility to health-care services and medicines is believed to be the main core of the right to health and the most important base of justice in health. The purpose of this study is to investigate the status of this right in the international community and the existing patterns as well as reviewing the challenges and opportunities in enhancing the right in Iran. Methods: To conduct the survey, some domestic and international sources, mainly on the internet, were employed, including papers, books, and reliable documents such as fact sheets, standards, interpretations, and conventions. The data were collected, summed up, and then they were analyzed and presented using a descriptive approach. Results: Right to health, in general, and right to accessibility to health-care services and medicines, in particular, is the right of each person to the enjoyment of the highest attainable standard of physical and mental health which is identified by four basic elements including availability, accessibility, acceptability and quality. According to the international documents and standards, the accessibility contains some aspects such as non-discrimination, physical, economic, and information, which partially, they have been taken into consideration in the laws and regulations of the Islamic Republic of Iran. To achieve the goals, governments are obliged to take relevant measures such as legislative, judicial and quasi-judicial as well as executives, administrative, and budgetary ones. To evaluate the fulfillment of right of accessibility, some standards have been introduced, one of which is a set of indicators published by the United Nations, which is considered as a main reference in the world. Conclusion: Despite some progress made in Iran in legislative and administrative aspects regarding the implementation of the right to accessibility, there are still some defects and shortcomings to reach the goals. Legal vacuum, insufficient budget, lack of enough attention to judicial and quasi-judicial practices, especially the role of inspection by ombudsman can be regarded as the main problems. Moreover, having a closer relationship with the relevant international organization is necessary. The necessity of reviewing and revising the existing laws and regulations is another tangible fact which can lead the country to resolve the problems and enhance the performance in this field.